2015
DOI: 10.1007/s10096-015-2331-z
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Escherichia coli isolates from the blood of haematological adult patients with bacteraemia: translocation from gut to blood requires the cooperation of multiple virulence factors

Abstract: The aim of the study was to investigate whether there are unique pathotypes of Escherichia coli capable of transmission from the gastrointestinal tract to the vascular bed. The study included E. coli strains isolated from clinical materials collected from 115 patients suffering from haematologic malignancies diagnosed with bacteraemia. The genotyping techniques established that 89 E. coli isolates from the blood had the same genotype as the E. coli from the patient’s bowel. The presence of 21 genes encoding vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 37 publications
3
28
1
1
Order By: Relevance
“…II, the sequence of three fragment genes, kspMTII [ 34 ] (synthesis capsule, group II), iha [ 35 ] (enterobactin Iha iron regulated gene homologue adhesion) and focG [ 34 ] (F1C fimbriae), were amplified. In multiplex PCR system III, the sequence of three fragment genes, iutA [ 36 ] (aerobactin receptor), fyuA [ 37 , 38 ] (yersiniabactin receptor) and ibeA [ 39 ] (invasion of brain endothelium A), were amplified.…”
Section: Methodsmentioning
confidence: 99%
“…II, the sequence of three fragment genes, kspMTII [ 34 ] (synthesis capsule, group II), iha [ 35 ] (enterobactin Iha iron regulated gene homologue adhesion) and focG [ 34 ] (F1C fimbriae), were amplified. In multiplex PCR system III, the sequence of three fragment genes, iutA [ 36 ] (aerobactin receptor), fyuA [ 37 , 38 ] (yersiniabactin receptor) and ibeA [ 39 ] (invasion of brain endothelium A), were amplified.…”
Section: Methodsmentioning
confidence: 99%
“…A collection of small association studies have attempted to establish the role of particular VFs associated with intestinal translocation and have all demonstrated that a collection, as opposed to individual VFs, are likely to be related to these events (55)(56)(57). In a recent study, Krawczyk et al (57) assessed VF profiles of ExPEC bacteraemia isolates derived from bowel translocation events in patients with haematological malignancy and concluded that the cooccurrence of multiple virulence genes was associated with an increased likelihood of intestinal translocation events.…”
Section: Vfs Associated With Bacteraemia and Gut Translocationmentioning
confidence: 99%
“…[1] The co-occurrence of multiple genes encoding papC , sfa , usp and cnf1 virulence factors probably predisposes Escherichia coli to translocation from the gastrointestinal tract to the vascular bed in patients with hematologic malignancies. [2] A recent study showed that differences in virulence gene prevalence between cystitis and pyelonephritis isolates could be limited to 8 genes. [3] However, the association of virulence gene and disease severity is still controversial.…”
Section: Introductionmentioning
confidence: 99%